Step
*
1
2
1
of Lemma
integral-rsum
1. d : ℤ
2. 0 < d
3. ∀[n:ℤ]. ∀[a,b:ℝ]. ∀[f:{f:{n..(n + (d - 1)) + 1-} ⟶ [rmin(a;b), rmax(a;b)] ⟶ℝ| 
                          ∀i:{n..(n + (d - 1)) + 1-}. ifun(λx.f[i;x];[rmin(a;b), rmax(a;b)])} ].
     (a_∫-b Σ{f[i;x] | n≤i≤n + (d - 1)} dx = Σ{a_∫-b f[i;x] dx | n≤i≤n + (d - 1)})
4. n : ℤ
5. a : ℝ
6. b : ℝ
7. f : {f:{n..(n + d) + 1-} ⟶ [rmin(a;b), rmax(a;b)] ⟶ℝ| 
        ∀i:{n..(n + d) + 1-}. ifun(λx.f[i;x];[rmin(a;b), rmax(a;b)])} 
⊢ a_∫-b Σ{f[i;x] | n≤i≤(n + d) - 1} + f[n + d;x] dx = (Σ{a_∫-b f[i;x] dx | n≤i≤(n + d) - 1} + a_∫-b f[n + d;x] dx)
BY
{ (Subst' (n + d) - 1 ~ n + (d - 1) 0 THENA Auto) }
1
1. d : ℤ
2. 0 < d
3. ∀[n:ℤ]. ∀[a,b:ℝ]. ∀[f:{f:{n..(n + (d - 1)) + 1-} ⟶ [rmin(a;b), rmax(a;b)] ⟶ℝ| 
                          ∀i:{n..(n + (d - 1)) + 1-}. ifun(λx.f[i;x];[rmin(a;b), rmax(a;b)])} ].
     (a_∫-b Σ{f[i;x] | n≤i≤n + (d - 1)} dx = Σ{a_∫-b f[i;x] dx | n≤i≤n + (d - 1)})
4. n : ℤ
5. a : ℝ
6. b : ℝ
7. f : {f:{n..(n + d) + 1-} ⟶ [rmin(a;b), rmax(a;b)] ⟶ℝ| 
        ∀i:{n..(n + d) + 1-}. ifun(λx.f[i;x];[rmin(a;b), rmax(a;b)])} 
⊢ a_∫-b Σ{f[i;x] | n≤i≤n + (d - 1)} + f[n + d;x] dx = (Σ{a_∫-b f[i;x] dx | n≤i≤n + (d - 1)} + a_∫-b f[n + d;x] dx)
Latex:
Latex:
1.  d  :  \mBbbZ{}
2.  0  <  d
3.  \mforall{}[n:\mBbbZ{}].  \mforall{}[a,b:\mBbbR{}].  \mforall{}[f:\{f:\{n..(n  +  (d  -  1))  +  1\msupminus{}\}  {}\mrightarrow{}  [rmin(a;b),  rmax(a;b)]  {}\mrightarrow{}\mBbbR{}| 
                                                    \mforall{}i:\{n..(n  +  (d  -  1))  +  1\msupminus{}\}.  ifun(\mlambda{}x.f[i;x];[rmin(a;b),  rmax(a;b)])\}  ].
          (a\_\mint{}\msupminus{}b  \mSigma{}\{f[i;x]  |  n\mleq{}i\mleq{}n  +  (d  -  1)\}  dx  =  \mSigma{}\{a\_\mint{}\msupminus{}b  f[i;x]  dx  |  n\mleq{}i\mleq{}n  +  (d  -  1)\})
4.  n  :  \mBbbZ{}
5.  a  :  \mBbbR{}
6.  b  :  \mBbbR{}
7.  f  :  \{f:\{n..(n  +  d)  +  1\msupminus{}\}  {}\mrightarrow{}  [rmin(a;b),  rmax(a;b)]  {}\mrightarrow{}\mBbbR{}| 
                \mforall{}i:\{n..(n  +  d)  +  1\msupminus{}\}.  ifun(\mlambda{}x.f[i;x];[rmin(a;b),  rmax(a;b)])\} 
\mvdash{}  a\_\mint{}\msupminus{}b  \mSigma{}\{f[i;x]  |  n\mleq{}i\mleq{}(n  +  d)  -  1\}  +  f[n  +  d;x]  dx
=  (\mSigma{}\{a\_\mint{}\msupminus{}b  f[i;x]  dx  |  n\mleq{}i\mleq{}(n  +  d)  -  1\}  +  a\_\mint{}\msupminus{}b  f[n  +  d;x]  dx)
By
Latex:
(Subst'  (n  +  d)  -  1  \msim{}  n  +  (d  -  1)  0  THENA  Auto)
Home
Index